2014
DOI: 10.7243/2053-5775-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Is dental extraction a risk factor for contracting HCV infection: Abs, RNA and genotype detection

Abstract: Background: The medical risk factor associated with hepatitis C virus (HCV) infection such as blood transfusion and surgery had been intensely studied in many countries. Up to 40% of patients infected with HCV may have non identifiable routes of viral acquisition. Dental extraction may be one of these risk factors. The purpose of the present study was to determine the existence of infection and the predominated HCV genotype among subjects with dental extraction. Material and methods: A case-control study invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…In a meta-analysis of 357 studies and literature review, dental treatment was suggested as a route of HCV transmission (47,48). Similar to the results of a previous research, tooth extraction was found to have an association with acquiring HCV infec- tion in the present study (49). Overall, it seems that tooth extraction by unprofessional staff, who work in substandard hygienic conditions in outpatient dental settings, are responsible for HCV transmission via tooth extraction in Iran.…”
Section: Discussionsupporting
confidence: 90%
“…In a meta-analysis of 357 studies and literature review, dental treatment was suggested as a route of HCV transmission (47,48). Similar to the results of a previous research, tooth extraction was found to have an association with acquiring HCV infec- tion in the present study (49). Overall, it seems that tooth extraction by unprofessional staff, who work in substandard hygienic conditions in outpatient dental settings, are responsible for HCV transmission via tooth extraction in Iran.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, a study [17] in Egypt showed no association between age and HCV infection. In this study, we observed that several unsafe invasive procedures such as dental procedure, previous stitches, surgical operation, schistosomiasis injection treatment, blood transfusion and [IV] fluid intake were significantly associated with a risk of HCV infections that is similar to the results of different studies [18][19][20]. The risk of HCV infection is significantly associated with unsafe practices in the community such as cupping, acupuncture, traditional cauterization, needle or sharp stick and tattooing and sharing shaving razors at community barbers which is [21,22].…”
Section: Discussionsupporting
confidence: 78%
“…This risk can be easily removed with standard precautions action [12, 13]. In a study in Iraq, it is reported that the extraction of teeth is a risk factor for developing HCV; the cleaning equipment and sterilization are needed [14]. A dentist belongs to a high risk group of suffering hepatitis.…”
Section: Discussionmentioning
confidence: 99%